An overview of biological applications and fundamentals of new inlet and vacuum ionization technologies. (20th November 2020) - Trimpin, Sarah; Marshall, Darrell D.; Karki, Santosh; Madarshahian, Sara; Hoang, Khoa; Meher, Anil K.; Pophristic, Milan; Richards, Alicia L.; Lietz, Christopher B.; Fischer, Joshua L.; Elia, Efstathios A.; Wang, Beixi; et al.
Abstract : Rationale: The developments of new ionization technologies based on processes previously unknown to mass spectrometry (MS) have gained significant momentum. Herein we address the importance of understanding these unique ionization processes, demonstrate the new capabilities currently unmet by other methods, and outline their considerable analytical potential. Methods: The inlet and vacuum ionization methods of solvent‐assisted ionization (SAI), matrix‐assisted ionization (MAI), and laserspray ionization can be used with commercial and dedicated ion sources producing ions from atmospheric or vacuum conditions for analyses of a variety of materials including drugs, lipids, and proteins introduced from well plates, pipet tips and plate surfaces with and without a laser using solid or solvent matrices. Mass spectrometers from various vendors are employed. Results: Results are presented highlighting strengths relative to ionization methods of electrospray ionization (ESI) and matrix‐assisted laser desorption/ionization. We demonstrate the utility of multi‐ionization platforms encompassing MAI, SAI, and ESI and enabling detection of what otherwise is missed, especially when directly analyzing mixtures. Unmatched robustness is achieved with dedicated vacuum MAI sources with mechanical introduction of the sample to the sub‐atmospheric pressure ( vacuum MAI). Simplicity and use of a wide array of matrices are attained using a conduit ( inlet ionization), preferably heated, with sample introduction from atmospheric pressure. Tissue, whole blood, urine (including mouse, chicken, and human origin), bacteria strains and chemical on‐probe reactions are analyzed directly and, especially in the case of vacuum ionization, without concern of carryover or instrument contamination. Conclusions: Examples are provided highlighting the exceptional analytical capabilities associated with the novel ionization processes in MS that reduce operational complexity while increasing speed and robustness, achieving mass spectra with low background for improved sensitivity, suggesting the potential of this simple ionization technology to drive MS into areas currently underserved, such as clinical and medical applications.